Short communication. Stallion sperm quality after combined ejaculate fractionation and colloidal centrifugation - Crespo, Francisco; Gosálvez, Jaime; Johnston, Stephen D.; de la Torre, Joaquina (Spanish Journal of Agricultural Research, 2015)
This study investigated the possible additive benefit of ejaculate fractionation and colloidal centrifugation on stallion sperm quality. Using an open-end artificial vagina, the sperm-rich fraction (FRAC-1) was separated from the rest of the ejaculate (FRAC-2) and a third sperm sample representing the combined ejaculate was reconstituted post-ejaculation (RAW). Each semen sample was processed for colloidal centrifugation. The percentage of abnormal spermatozoa was 17.8 ± 7.0% in RAW and 14.6 ± 9.5% in FRAC-1 but decreased to 11.4 ± 4.7% and 9.6 ± 6.9% respectively, after colloidal centrifugation. A sperm DNA fragmentation index of 10.9 ± 5.1% was observed in RAW and 7.5 ± 2.4% in FRAC-1 semen collected with the AV but this decreased to 7.8 ± 2.8% and 5.2 ± 2.3% after colloidal centrifugation. The rate of increase in sperm DNA fragmentation during the first 6 h of incubation at 37 ºC was 1.8 ± 0.9% per hour in RAW semen and 2.0 ± 2.0% per hour in FRAC-1 but this significantly decreased to 1.3 ± 1.4% and 0.9 ± 0.8% respectively after colloidal centrifugation. While stallion seminal characteristics can be improved using colloidal centrifugation, further enhancement is possible if the ejaculate is initially fractionated.